Adherence to the 2018 AHA cholesterol management guideline in hyperlipidemia treatment among adults in an outpatient setting - Behdani, Bahere; Kazemi, Toba; Zardast, Mahmood; Khosravi Bizhaem, Saeede; Jafari, Shima (Frontiers in Cardiovascular Medicine, 2024)
Background Although evidence-based guidelines and effective treatments exist for dyslipidemia, a significant disparity remains between guidelines and clinical practice. In this study, we investigated adherence to statin therapy per the 2018 ACC/AHA Guideline recommendations. Methods This is a retrospective, descriptive-analytical study involving 1,224 individuals who presented to the laboratories located in Birjand, Eastern Iran, from June 2022 to March 2023. Analyses were conducted on 700 patients. Data collection utilized a checklist and serum value measurements of laboratory factors deemed necessary for the study. Results Treatment was administered per the guidelines for 348 out of the 700 patients (49.7%). With 60.7%, the diabetes group exhibited the highest level of adherence to guidelines. In the atherosclerotic cardiovascular disease (ASCVD) group, 31.7% followed the recommendations. The lowest adherence rates were in groups with a 10-year ASCVD risk score of ≥20% and severe hypercholesterolemia, respectively (0% and 2.8%). In our study, atorvastatin was the most frequently prescribed statin, with the majority of patients consuming a moderate-intensity statin. None of the severely hypercholesterolemic patients achieved the LDL goal. Moreover, LDL-C goal achievement was low among the ASCVD group and those with an ASCVD risk score of ≥20%. Conclusion Patients with hypercholesterolemia adhere inadequately to the AHA Guideline. Consequently, training courses are needed to inform medical doctors, particularly general practitioners, of the latest dyslipidemia treatment recommendations as the AHA advises.